Role of Cellular Tumor Necrosis Factor Receptor-Associated Factors in NF-κB Activation and Lymphocyte Transformation by Herpesvirus Saimiri STP - Lee, Heuiran (American Society for Microbiology, 1999)
The STP oncoproteins of the herpesvirus saimiri (HVS) subgroup A strain 11 and subgroup C strain 488 are now found to be stably associated with tumor necrosis factor receptor-associated factor (TRAF) 1, 2, or 3. Mutational analyses identified residues of PXQXT/S in STP-A11 as critical for TRAF association. In addition, a somewhat divergent region of STP-C488 is critical for TRAF association. Mutational analysis also revealed that STP-C488 induced NF-κB activation that was correlated with its ability to associate with TRAFs. The HVS STP-C488 P(10)→R mutant was deficient in human T-lymphocyte transformation to interleukin-2-independent growth but showed wild-type phenotype for marmoset T-lymphocyte transformation in vitro and in vivo. The STP-C488 P(10)→R mutant was also defective in Rat-1 fibroblast transformation, and fibroblast cell transformation was blocked by a TRAF2 dominant-negative mutant. These data implicate TRAFs in STP-C488-mediated transformation of human lymphocytes and rodent fibroblasts. Other factors are implicated in immortalization of common marmoset T lymphocytes and may also be critical in the transformation of human lymphocytes and rodent fibroblasts.